Restatements – koncepcja i zastosowanie - Supernat, Jerzy (E-Wydawnictwo. Prawnicza i Ekonomiczna Biblioteka Cyfrowa. Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
Restatements have a decidedly American origin but these days the concept finds its application in the ReNEUAL project whose aim is to rationalize, clarify and, on the margins, to improve European Union administrative law.
Keywords: ReNEUAL; restatements; European Union administrative law